Noninvasive High-Speed Photoacoustic Tomography of Cerebral Hemodynamics in Awake-Moving Rats. Issue 8 (August 2015) - Tang, Jianbo; Xi, Lei; Zhou, Junli; Huang, Hua; Zhang, Tao; Carney, Paul R; Jiang, Huabei
We present a noninvasive method of photoacoustic tomography (PAT) for imaging cerebral hemodynamics in awake-moving rats. The wearable PAT (wPAT) system has a size of 15 mm in height and 33 mm in diameter, and a weight of 8 g (excluding cabling). The wPAT achieved an imaging rate of 3.33 frames/s with a lateral resolution of 243 μ m. Animal experiments were designed to show wPAT feasibility for imaging cerebral hemodynamics on awake-moving animals. Results showed that the cerebral oxy-hemoglobin and deoxy-hemoglobin changed significantly in response to hyperoxia; and, after the injection of pentylenetetrazol (PTZ), cerebral blood volume changed faster over time and larger in amplitude for rats in awake-moving state compared with rats under anesthesia. By providing a light-weight, high-resolution technology for in vivo monitoring of cerebral hemodynamics in awake-behaving animals, it will be possible to develop a comprehensive understanding on how activity alters hemodynamics in normal and diseased states.